2011
DOI: 10.1016/j.gde.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate regulation of mRNA decay networks by GU-rich elements and CELF1

Abstract: The GU-rich element (GRE) was identified as a conserved sequence enriched in the 3′ UTR of human transcripts that exhibited rapid mRNA turnover. In mammalian cells, binding to GREs by the protein CELF1 coordinates mRNA decay of networks of transcripts involved in cell growth, migration, and apoptosis. Depending on the context, GREs and CELF1 also regulate pre-mRNA splicing and translation. GREs are highly conserved throughout evolution and play important roles in development of organisms ranging from worms to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 70 publications
2
27
0
1
Order By: Relevance
“…The decay of ARE-containing mRNAs begins with either synchronous or distributive poly(A) shortening 42 , with the subsequent steps targeting the body of the mRNA from both ends (Box 1, panel A) via the actions of the 5′-3′ and 3′-5′ exonucleases 43 . There are other cis-acting instability elements, the best studied of which are the GU-rich elements (GREs) 44 . GREs function in post-transcriptional regulons involving pre-mRNA splicing and mRNA decay that are coordinated by binding of the CUG-BP Elav-like family (CELF) proteins, the best known of which is CELF1 (also called CUG-BP1) 45,46 .…”
Section: Are-mediated Mrna Decaymentioning
confidence: 99%
“…The decay of ARE-containing mRNAs begins with either synchronous or distributive poly(A) shortening 42 , with the subsequent steps targeting the body of the mRNA from both ends (Box 1, panel A) via the actions of the 5′-3′ and 3′-5′ exonucleases 43 . There are other cis-acting instability elements, the best studied of which are the GU-rich elements (GREs) 44 . GREs function in post-transcriptional regulons involving pre-mRNA splicing and mRNA decay that are coordinated by binding of the CUG-BP Elav-like family (CELF) proteins, the best known of which is CELF1 (also called CUG-BP1) 45,46 .…”
Section: Are-mediated Mrna Decaymentioning
confidence: 99%
“…For example, the HuR protein influences decay or translation of numerous mRNA targets involved in cell proliferation, survival, evasion of immune recognition, metastasis and angiogenesis 19 . Like HuR, CELF1 and its target mRNAs are involved in post-transcriptional regulatory networks that control cell growth, activation and differentiation 20 . Because of this, inappropriate expression of a single RBP can impact a wide-range of cellular functions in a coordinated fashion to profoundly change the phenotype of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of CUGBP1 in HeLa cells stabilizes these mRNAs, while the insertion of the GREs from these transcripts into the stable β-globin mRNA reduces stability of β-globin mRNA (Vlasova et al, 2008). Analysis of CUGBP1 associated transcripts in HeLa cells has been performed by this group and has shown that CUGBP1 binds to hundreds of transcripts containing the GRE element (Rattenbacher et al, 2010; Vlasova-St Luis et al, 2011). Because CUGBP1 contains three RNA Binding Domains (RBD, see figure 1), further studies have examined the binding specificity of these domains and showed that the first two RBDs of CUGBP1 interact with GRE and CUG repeats (Edwards et al, 2011; Teplova et al, 2010).…”
Section: A Multi-functional Cug Triplet Repeat Binding Protein Cumentioning
confidence: 99%